Detection of volatile biomarkers of therapeutic radiation in breath - Phillips, Michael; Byrnes, Richard; Cataneo, Renee N; Chaturvedi, Anirudh; Kaplan, Peter D; Libardoni, Mark; Mehta, Vivek; Mundada, Mayur; Patel, Urvish; Ramakrishna, Naren; Schiff, Peter B; Zhang, Xiang (Journal of breath research, 2013)
Breath testing could provide a rational tool for radiation biodosimetry because radiation causes distinct stress-producing molecular damage, notably an increased production of reactive oxygen species. The resulting oxidative stress accelerates lipid peroxidation of polyunsaturated fatty acids, liberating alkanes and alkane metabolites that are excreted in the breath as volatile organic compounds (VOCs). Breath tests were performed before and after radiation therapy over five days in 31 subjects receiving daily fractionated doses: 180-400 cGy d(-1) standard radiotherapy (n = 26), or 700-1200 cGy d(-1) high-dose stereotactic body radiotherapy (n = 5). Breath VOCs were assayed using comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry. Multiple Monte Carlo simulations identified approximately 50 VOCs as greater-than-chance biomarkers of radiation on all five days of the study. A consistent subset of 15 VOCs was observed at all time points. A radiation response function was built by combining these biomarkers and the resulting dose-effect curve was significantly elevated at all exposures ⩾1.8 Gy. Cross-validated binary algorithms identified radiation exposures ⩾1.8 Gy with 99% accuracy, and ⩾5 Gy with 78% accuracy. In this proof of principal study of breath VOCs, we built a preliminary radiation response function based on 15 VOCs that appears to identify exposure to localized doses of 1.8 Gy and higher. VOC breath testing could provide a new tool for rapid and non-invasive radiation biodosimetry.